Tax Reform Elements and Taxpayer Compliance: The Moderating Role of Tax Consultants in Indonesia - Laksito, Herry; Purwiyanti, Deviana Wahyu (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Tax revenue constitutes the primary source of state funding in Indonesia, yet persistent shortfalls in collection and low taxpayer compliance remain significant challenges, particularly among individual taxpayers. Comprehensive tax reforms have been implemented to enhance organizational structure, human resource quality, information technology and databases, business processes, and regulatory effectiveness, aiming to foster voluntary compliance. However, the intermediary role of tax consultants in interpreting and applying these reforms introduces complexity, with limited understanding of how they moderate reform impacts. This study examines the influence of each tax reform element on individual taxpayer compliance, with the role of tax consultants as a moderating variable. Employing a case study approach at the Central Java I Regional Tax Office, data were collected through questionnaires from individual taxpayers and analyzed using Structural Equation Modeling. Results indicate that all five reform elements positively and significantly affect taxpayer compliance. The role of tax consultants strengthens the effects of organizational restructuring and human resource quality, shows no significant moderation on information technology and business process quality, and unexpectedly weakens the influence of regulatory effectiveness. These findings imply that tax authorities should prioritize human-centered reforms alongside accelerated digitalization to promote independent compliance.